Fostering student's critical reading through technology integrated instruction - Sutrisno, Djoko (Teaching English as a Foreign Language Journal, 2022)
Students today grow up with technology devices at home and school, which transform how they study. Future education technology will alter teaching and learning by making new gadgets available to teachers and students. Thus, the study was meant to explore the impact of multimedia technology-integrated instruction on upper primary students' critical reading learning in one of Indonesia's private schools. To further comprehend the outcomes, a mixed methods study was conducted. Purposive sampling was used to choose 30 pupils as research samples. For three months, the participants were taught at least three science sessions per week utilizing multimedia technology. Instruments such as open-ended questions and questionnaires were used to collect data. The quantitative results from the questionnaire were examined and inferred using an inferential statistical t-test and descriptive statistical mean and standard deviation with a significance level of p 0.05. The qualitative data from open-ended questions were analyzed using the grounded theory coding technique. According to the findings, students were incredibly satisfied with learning science through multimedia technology because it made the lessons easier to grasp and more likely to engage, easy, and interesting. As a result, the researchers concluded that introducing multimedia technology into education had a considerable positive influence on raising student learning satisfaction and improving critical reading skills The post-test scores in the group that utilized multimedia technology are noticeably higher when the two groups are compared.